Estrategias metodológicas para la iniciación de la lectoescritura en el proceso enseñanza aprendizaje de los niños y niñas del primer año de educación básica del Jardín de Infantes Mixto Amada Agurto de Galarza de la ciudad de Machala, período lectivo 2012-2013. - Morán Zambrano, Marlene Victoria (2013)
The investigative process allowed to conclude that the main strategies used by kindergarten teachers for initiation of literacy learning are traditional and passive court, based mainly on mechanical filling ranging from pre leaves with sample letters and passive listening reading uninteresting because most teachers are unaware of active and participatory methodologies to start reading and writing which causes children not acquire the linguistic and motor skills necessary for correct oral and written communication.